2014
DOI: 10.5851/kosfa.2014.34.6.829
|View full text |Cite
|
Sign up to set email alerts
|

Lysate of Probiotic Lactobacillus plantarum K8 Modulate the Mucosal Inflammatory System in Dextran Sulfate Sodium-induced Colitic Rats

Abstract: Inflammatory bowel disease (IBD) is caused by dysregulation of colon mucosal immunity and mucosal epithelial barrier function. Recent studies have reported that lipoteichoic acid (LTA) from Lactobacillus plantarum K8 reduces excessive production of pro-inflammatory cytokine. In this study, we investigated the preventive effects of lysate of Lb. plantarum K8 in dextran sulfate sodium (DSS)-induced colitis. Male Sprague-Dawley rats were orally pretreated with lysate of Lb. plantarum K8 (low dose or high dose) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
3
7
0
Order By: Relevance
“…DSS-induced infiltration of neutrophils and macrophages into mouse colonic mucosa induced the secretion of considerable amounts of inflammatory cytokines and MPO, and the treatment with L. plantarum alleviated this aggravated inflammatory status. The results of the present study were consistent with the reported effects of LAB, including a reduction in the levels of proinflammatory mediators (Ahn et al, 2014;Wirtz et al, 2017). IL-6, IL-1β and TNF-α are essential proinflammatory mediators that accumulate in large quantities within the colon tissues with IBD symptoms, and NF-κB is a crucial regulator of these intracellular signaling pathways.…”
Section: Discussionsupporting
confidence: 93%
“…DSS-induced infiltration of neutrophils and macrophages into mouse colonic mucosa induced the secretion of considerable amounts of inflammatory cytokines and MPO, and the treatment with L. plantarum alleviated this aggravated inflammatory status. The results of the present study were consistent with the reported effects of LAB, including a reduction in the levels of proinflammatory mediators (Ahn et al, 2014;Wirtz et al, 2017). IL-6, IL-1β and TNF-α are essential proinflammatory mediators that accumulate in large quantities within the colon tissues with IBD symptoms, and NF-κB is a crucial regulator of these intracellular signaling pathways.…”
Section: Discussionsupporting
confidence: 93%
“…L. plantarum has been shown to not only help maintain intestinal permeability, but also has significant antioxidant capacity (24). L. plantarum appears to be an effective therapeutic strategy for colitis, intestinal bowel syndrome (IBD) and Crohn's disease (1). Psychotropic effects such as depression or anxiety have been ameliorated by L. plantarum supplementation via modulation of the hippocampal brain-derived neurotrophic factor and striatum monoamine neurotransmitter levels (15).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has reported on the beneficial effects of probiotic lysates on various diseases. Several studies have indicated that Lactobacillus lysates ameliorate colitis by strengthening gut barrier function and modulating the mucosal inflammatory system [ 8 , 20 ]. Moreover, Lactobacillus lysates enhance antitumor immune responses [ 21 ] and improve hypercholesterolemia [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to concerns about the safety and usefulness of viable probiotics, probiotic lysates have recently gained attention as an alternative [ 6 ]. Both probiotics and probiotic lysates have demonstrated beneficial effects on various diseases and conditions, such as colitis, inflammation, and tumors [ 7 , 8 ]. Interestingly, several studies have shown that probiotic lysates ameliorate obesity by decreasing body weight, especially adipose tissue weight, lowering total cholesterol, and reducing the expression of adipogenic factors in vitro and in vivo [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%